Improving reading comprehension in descriptive text with shared reading method - Nurjayati; Khoirul Wafa; Moh Zainuddin; Nurjayati; Khoirul Wafa; Moh Zainuddin (INTENS (International Journal of English Education and Linguistics), 2024)
"This research aims to improve students' reading comprehension skills in English lessons in descriptive texts using the shared reading method. Research includes Classroom Action Research (PTK). The subjects of this research were 15 students in class X-A MA Sunan Bonang Ponco for the 2023/2024 academic year. This research aims to improve students' reading comprehension skills in descriptive text. This research was carried out in two cycles, each consisting of planning, implementing actions, observing, and reflecting. Data was collected through quantitative and qualitative data. The results of this research indicate that there is an increase in students' reading comprehension skills. The average pre-test score was 46.13%. The average value of post-test 1 is 66.93. the average post-test two was 82.13. it shows that the score and average in the second cycle are better than in the first cycle. The percentage of students who scored >75 has increased. In the pre-test, there were two students (13.33%) who got a score of >75 and above. In the post-test cycle 1, there were four students (26.66%) who scored >75 and above. Post-test cycle, two students who obtained a score >75 were 14 students (93.33%). Students' ability to understand reading in descriptive texts increases and becomes better from the first meeting to the next meeting using the shared reading method."